2018
DOI: 10.1111/bdi.12665
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of monotherapies for psychiatric hospitalization risk in bipolar disorders

Abstract: This largest reported retrospective observational study on bipolar disorders pharmacotherapy to date demonstrates that the majority of patients end monotherapy within 2 months after treatment start. The risk of psychiatric hospitalization varied almost two-fold across individual medications. The data add to the evidence favoring lithium and mood stabilizer use in short-term bipolar disorder management. The findings that the dopaminergic drugs aripiprazole and bupropion had better outcomes than other members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Existing literature has not addressed the impact of antidepressants prescribed prior to a bipolar disorder diagnosis, while studies focusing on their effects post-diagnosis reveal mixed results regarding psychiatric hospitalization rates. For instance, a database study of 190,824 patients with bipolar or schizoaffective disorder over three months on average reported that valproic acid, aripiprazole, and bupropion were associated with lower hospitalization rates than lithium carbonate, while most antidepressants were correlated with higher rates [Nestsiarovich et al 2018]. On the other hand, one cohort study of 519 hospitalized bipolar patients over a year showed that no form of pharmacotherapy, including antidepressants, signi cantly affected rehospitalization rates Patients with a history of MDD diagnosis experienced lower hospitalization rates for all causes compared to those without such a history.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has not addressed the impact of antidepressants prescribed prior to a bipolar disorder diagnosis, while studies focusing on their effects post-diagnosis reveal mixed results regarding psychiatric hospitalization rates. For instance, a database study of 190,824 patients with bipolar or schizoaffective disorder over three months on average reported that valproic acid, aripiprazole, and bupropion were associated with lower hospitalization rates than lithium carbonate, while most antidepressants were correlated with higher rates [Nestsiarovich et al 2018]. On the other hand, one cohort study of 519 hospitalized bipolar patients over a year showed that no form of pharmacotherapy, including antidepressants, signi cantly affected rehospitalization rates Patients with a history of MDD diagnosis experienced lower hospitalization rates for all causes compared to those without such a history.…”
Section: Discussionmentioning
confidence: 99%